2006
DOI: 10.1007/s10826-006-9088-z
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Parenting Class Curriculum for Parents of Young Children: Parenting the Strong-Willed Child

Abstract: Young children with high levels of acting out behaviors present a challenge for families, caregivers, and the childcare system. The Parenting the Strong-Willed Child (PSWC) parenting class curriculum program is a 6-week, group based parent education program designed for parents of children with noncompliance problems (ages 2-8). The PSWC program was offered at no cost to parents enrolled in 8 Head Start centers, and parents were invited to participate in a program evaluation study. Seventy-one families enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Significantly, African American mothers who participated in parenting classes displayed fewer parental detachment behaviors over time as compared with mothers in the reference group. These results support the work of Conners et al (2006), which found that parenting classes helped parents relax their strict discipline behaviors and lower their levels of emotional intensity in the discipline encounter.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Significantly, African American mothers who participated in parenting classes displayed fewer parental detachment behaviors over time as compared with mothers in the reference group. These results support the work of Conners et al (2006), which found that parenting classes helped parents relax their strict discipline behaviors and lower their levels of emotional intensity in the discipline encounter.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…More than 40% of Head Start mothers Downloaded by [Northern Kentucky University] at 19:11 10 June 2016 displayed high rates of harsh or physically negative discipline, which is also a major risk factor. An empirical study conducted by Conners et al (2006) provided six-week group education programs for parents at eight Head Start centers. The researchers found that participants of parenting programs improved their parenting behavior and reported significant reductions in their own levels of stress.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This program trains parents to increase positive attention for good behavior, provide appropriate consequences, provide clear instructions, and other basic concepts related to behavior modification. In an independent evaluation of 71 parents who participated in the PSWC program, results indicated significant improvements in child behavior problems (both frequency and intensity, as reported by parents) and self-reported parenting behavior (Conners et al 2007). As such, this study also provides evidence for effectively treating children through a parent intervention.…”
Section: Pt With Oppositional/conduct Problemsmentioning
confidence: 99%
“…The Group Curriculum (GC) program has been examined in an uncontrolled trial, and the findings suggest that parent and child positive behavior change occurs with implementation of the program (Conners et al, 2007). Furthermore, parents reported general satisfaction with the GC program.…”
Section: Introductionmentioning
confidence: 99%